Analysis of antimicrobials' consumption profile in a University Hospital of Western Paraná, Brazil - Luciane de Fátima Caldeira; Marcelo Nascimento Burattini (Universidade de São Paulo, 2009)
The objective of this study was to analyze the variation in antimicrobials' consumption and the costs related to their use at a University Hospital between 1999 and 2004. The annual consumption of nine antimicrobials, expressed in DDD/100 patients-day, and the direct costs with their acquisition were evaluated. Analysis of variance and regression techniques were used to compare data, considering a significance level of 5%. The most consumed antimicrobials were amikacin and ceftriaxone. In general, antimicrobials consumption, expressed in DDD/100 patients-day, increased from 9.21 in 1999 to 25.08 in 2004 (p<0.0001). When analyzing antimicrobial consumption as related to specific hospital units, the ICU showed the highest consumption followed by Chemotherapy and Medical Clinical units, respectively. In addition, the number of patients-day increased from 2671/month in 1999 to 3502/month in 2004, p<0.0001. As a consequence, total expenditure with antimicrobials increased from R$ 98.89 per 100 patients-day in 1999 to R$ 731.26 in 2004, p<0.0001. Between 1999 and 2004 significant increases in both consumption and financial expenditure with antimicrobials were observed. O trabalho teve por objetivo analisar a variação do consumo e gastos financeiros com antimicrobianos em Hospital Universitário entre 1999 e 2004. Analisou-se 9 antimicrobianos, sendo o consumo expresso em DDDs/100 pacientes-dia e o preço médio de compra obtido do relatório da farmácia hospitalar. As variações anuais no consumo, o consumo por tipo de unidades de internação e gastos com cada antimicrobiano foram estudadas por análise de variância. Adotou-se 5% como limiar de significância. Os antimicrobianos mais consumidos no período foram amicacina e ceftriaxona. Observou-se aumento no consumo dos antimicrobianos selecionados de 9,21 DDDs/100 pacientes-dia em 1999 para 25,08 em 2004 (p<0,0001). Entre as unidades de internação, a UTI apresentou o maior consumo médio, seguindo-se as unidades de Quimioterapia e Clínica Médica. A média mensal de pacientes-dia atendidos aumentou de 2671 em 1999 para 3502 em 2004 (p<0,0001). Observou-se aumento significativo nos gastos totais com antimicrobianos no período (R$ 98,89 x R$ 731,26 por 100 pacientes-dia entre 1999 e 2004, p<0,0001). Observou-se aumento significativo tanto na utilização quanto no gasto financeiro por 100 pacientes-dia diretamente relacionado à aquisição dos antimicrobianos estudados.